Integrative Omics Analyses Reveal the Effects of Copper Ions on Salvianolic Acid Biosynthesis - Xiang, Yaping; Wang, Xiaoxiao; Song, Wei; Du, Jinfa; Yin, Xiaojian (Frontiers in Plant Science, 2021)
Salvianolic acids (SalAs), a group of secondary metabolites produced by Salvia miltiorrhiza, are widely used for treating cerebrovascular diseases. Copper is recognized as a necessary microelement and plays an essential role in plant growth. At present, the effect of copper on the biosynthesis of SalAs is unknown. Here, an integrated metabolomic and transcriptomic approach coupled with biochemical analyses was employed to dissect the mechanisms by which copper ions induced the biosynthesis of SalAs. In this study, we identified that a low concentration (5 µM ) of copper ions could promote growth of S. miltiorrhiza and the biosynthesis of SalAs. Results of the metabolomics analysis showed that 160 metabolites (90 increased and 70 decreased) were significantly changed in S. miltiorrhiza treated with low concentration of copper ions. The differential metabolites were mainly involved in amino acid metabolism, the pentose phosphate pathway, and carbon fixation in photosynthetic organisms. The contents of chlorophyll a, chlorophyll b, and total chlorophyll were significantly increased in leaves of low concentration of copper treated S. miltiorrhiza plants. Importantly, core SalA biosynthetic genes (laccases and rosmarinic acid synthase), SalA biosynthesis related transcription factors (MYBs and zinc finger CCCH domain-containing protein 33), and chloroplast proteins encoding genes (blue copper protein and chlorophyll binding protein) were upregulated in the treated samples as indicated by a comprehensive transcriptomic analysis. Bioinformatics and enzyme activity analyses showed that laccase 20 contained copper binding motifs and its activity in low concentration of copper ions-treated S. miltiorrhiza was much higher than that in the control. Our results demonstrate that copper ions enhance the accumulation of SalAs might be through regulating laccase 20, MYBs and zinc finger transcription factors, and photosynthetic genes.